Comparison of stochastic fault detection and classification algorithms for nonlinear chemical processes. (2nd November 2017) - Du, Yuncheng; Budman, Hector; Duever, Thomas A.
Highlights: Generalized polynomial chaos (gPC) and Gaussian Process (GP) are used for FDD. The advantages and limitations of gPC and GP model-based FDD are investigated. Optimal selection of data is studied for gPC models via sensitivity analysis. Model calibration is developed for GP model to minimize the model discrepancy. Abstract: This paper presents a comparative study of two methods to identify and classify intermittent stochastic faults occurring in a dynamic nonlinear chemical process. The methods are based on two popular stochastic modelling techniques, i.e., generalized polynomial chaos expansion (gPC) and Gaussian Process (GP). The goal is to assess which method is more efficient for fault detection and diagnosis (FDD) when using models with parametric uncertainty, and to show the capabilities and drawbacks of each method. The first method is based on a first-principle model combined with a gPC expansion to represent the uncertainty. Resulting statistics such as probability density functions (PDFs) of the measured variables is further used to infer the intermittent faults. For the second method, a GP model is used to project multiple inputs into a univariate model response from which the fault can be identified based on a minimum distance criterion. The performance of the proposed FDD algorithms is illustrated through two examples: (i) a chemical process involving two continuous, stirred tank reactors (CSTRs) and a flash tank separator, and (ii) the Tennessee Eastman benchmark problem.